Telehealth: from the abstract to necessity to competency. Issue 7 (3rd April 2021) - Adams, Jennifer E.; Ecker, David J.
Abstract: The COVID‐19 pandemic caused significant disruption in medical education. With disruption comes the opportunity for innovation. Telehealth had been growing rapidly in many fields of medicine prior to the pandemic; however, the necessities of social distancing, scarcity of personal protective equipment, and mandates to prevent unnecessary exposures for healthcare workers and patients alike, brought opportunities for the exponential expansion of telehealth. With the expansion of telehealth services came the need to expand the curriculum in telehealth to prepare medical students to return to vastly transformed clinical settings as well as prepare them for a future clinical landscape likely to incorporate telehealth to a much greater degree. The University of Colorado School of Medicine (CUSOM) rapidly developed a course in telehealth to prepare students for this changing clinical environment. Simultaneously, a faculty development curriculum was created to support clinical faculty new to telehealth in basic skills and teaching in a virtual environment. Lastly, adaptations were made to the summative Clinical Practice Exam administered to students at the completion of clerkships to incorporate telehealth. Recognizing the importance of achieving competence in telehealth, the CUSOM has taken steps to invest in the development of comprehensive and integrated telehealth curricula. Many creative and innovative solutions have been adopted in the wake of this pandemic to allow medical education to continue despite many hurdles and barriers; many of these will not persist past the pandemic. However, we expect telehealth clinical skills and the curricula developed to support them to remain relevant long past the time when the COVID‐19 pandemic has faded into history.